The Occurrence Of Coccidiosis In Quails (Coturnix Japonica) At Different Ages - Abdul Ra’uf Zaidee (2018)
The southeast Asia is believed to be the origin of Japanese quails breed. It is extensively used as table birds and pet birds. In Malaysia, quails are reared as meat for protein source. Many reasearch studied about coccidiosis and quails, but none of them are specifically focus on occurence of coccidiosis in different quails breed at different age. This study will focus on finding of the effect of different quails breed towards coccidiosis occurence, alongside the effect of quails age against the occurence of coccidiosis. Different type of breed may be affected differently, and the occurence of coccidiosis may vary with different age of quails. Total of 70 faecal sample were collected from two groups of different ages of quails. The oocysts of Eimeria were observed and the oocysts per gram(OPG) of faeces were calculated. It was hypothesized that OPG varied with different ages of quails.This research contributes information related to the occurrence of coccidiosis that would vary with the different ages of quails.